La inseguridad jurídica al derecho a la sucesión y al patrimonio, afecta al testamento solemne - Pinos Murillo, Lety Magaly (2013)
The Present Legal Research had as objective research floors unprocessed doctrinal, legal and empirical Around the Rules Regulating the granting of solemn testament in Ecuador, in order to propose a reform proposal to the Arts. 1043, 1050, 1054, 1055, 1056, 1058 and 1063 of the Civil Code in order to ensure legal certainty in the succession law and equity. To achieve this, they made no doctrinaire Legal Analysis and Problem, But where we determined the Champs tales problematic provisions Regulations, Making The Same That justified the United Nations Research Topic That has not deserved the importance of the case, and the Formulation of the Oriento hypothesis and Field Work The Same Research. Yes Theoretical Framework Development Methods base raised (DESCRIPTIVE, analytical and field), and That Once obtained the results do Corresponding Research and Analysis, yeah Step to develop legal reform proposal will Normative countryside solemn awarded in Ecuador, within the framework of constitutional law. Regulatory act WELL AS ALL must be developed in compliance with Legal provisions in the case solemn will raise a REFORM WAS needed inconsistencies and inadequacies Policies Civil Code, paragraph Avoid That law affect the assets of the heirs. De Finally, the results to be achieved with the present proposal to reform the Civil Code, the son: Ensuring The Legal Certainty solemn testament Celebration of Me Succession By cause of death will not affect Constitutional Rights And You Will Be the testator not violated by y applying subjectivities discretionary criteria